Tourists and 'philosophers': Nature as a medium to consciousness and transcendence in spiritual tourism. (March 2023) - Wang, Shaohua; Blasco, Dani; Hamzah, Amran; Verschuuren, Bas
Abstract: Nature is a vital context for transcendent experiences fostering the spiritual dimensions of humankind. Analysing data from protected areas in China, this paper investigates the ways in which spirituality permeates nature-based tourism. A thematic analysis was undertaken to interpret 27 semi-structured in-depth interviews with professionals and tourists. Findings enable the construction of a hierarchical framework of spiritual tourism achievement and highlight the need to create links between protected areas, tourists, and 'mediums'. Nature is acknowledged as a means of overcoming spiritual emptiness in a secular nation where religions function in a limited way and traditional wisdom is undervalued. This study proposes a nature-based, philosophy-oriented tourism development model, which sheds light on theoretical and industrial domains alike. Highlights: Discuss the conceptual confusion and vacuity of theory in spiritual tourism Identify a hierarchical framework of spiritual tourism achievement Propose an association between tourists, protected areas, and 'mediums' How can Chinese people console their spirits and overcome spiritual emptiness Expect future research on gender issues, indigenous people, and sustainability